OPTIMALISASI PENGELOLAAN KEBUN RAYA BOGOR DALAM PERANNYA SEBAGAI AREA KONSERVASI EK-SITU DAN REKREASI - , Rinawati Eko P.L. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Ecosystem management in artificial ecosystem with multifunction would need to apply a multidisciplinary approach to attaining optimalization. Carrying capacity concept implements to design Bogor Botanical Gardens (BBG) optimalization management according to multidisciplinary approach (collection management, collection mapping and visitor willingness to pay). The aim of this research is to study the BBG living-collection characteristic, mapping collection, measure visitor willingness to pay, recreation carrying capacities and promote an elaboration in BBG management. This research used descriptive and surveys methods continued with mapping BBG living collection and visitor willingness to pay measurement. Visitor willingness to pay will be used to capture visitor preferences in BBG management strategy by considering an ideal visitor crowding. The results shows there are 3 planting group of BBG living-collection according to their taxonomy. There are Pterydophyta (96%), Spermatophyta (2%) and Magnoliophyta (2%). BBG has 146 living collection registered as Red List and 1110 as critical collection. Critical collections used to describe when he collection only has one specimen living in BBG. According to the distribution of Red List collection BBG has 5 planting area based collection taxonomy, 3 area with high level of threatened (Vak VII.B, VIII.D and XXV.A) and 1 area with high critical collection (XI.B). Willingness to pay suggest that visitor ideal ticket is Rp. 9.561,00, the willingness to pay for restricted access about Rp. 10.000,00 and willingness to pay for visitor restricted about Rp. 19.500,00. The recreation carrying capacities formulated according to visitors preferences crowding level who willing to pay for restricted access and restricted visitor. Cross analyst has results maximum visitor crowding is between 5000 until 8000 visitor per day. According to that BBG optimilization management could be arrange according to visitor preferences crowding level and price targeting in a different ticket tariff. If visitor crowding about 5000 (weekdays) we suggest Rp. 9.500,00.. If visitor crowding about 5000 â 8000 (weekend) we suggest Rp. 10.000,00 and Rp. 19.500,00 if visitor crowding predicted as 8000 vsitor per day (holiday peaks)